Oblique effect in visual mismatch negativity - Takács, Endre; Sulykos, István; Czigler, István; Barkaszi, Irén; Balázs, László (Frontiers in Human Neuroscience, 2013)
We investigated whether visual orientation anisotropies (known as oblique effect) exist in non-attended visual changes using event-related potentials (ERP). We recorded visual mismatch negativity (vMMN) which signals violation of sequential regularities. In the visual periphery unattended, task-irrelevant Gábor patches were displayed in an oddball sequence while subjects performed a tracking task in the central field. A moderate change (50°) in the orientation of stimuli revealed no consistent change-related components. However we found orientation-related differences around 170 ms in occipito-temporal areas in the amplitude of the ERPs evoked by standard stimuli. In a supplementary experiment we determined the amount of orientation difference that is needed for change detection in an active, attended paradigm. Results exhibited the classical oblique effect; subjects detected 10° deviations from cardinal directions, while threshold from oblique directions was 17°. These results provide evidence that perception of change could be accomplished at significantly smaller thresholds, than what elicits vMMN. In Experiment2 we increased the orientation change to 90°. Deviant-minus-standard difference was negative in occipito-parietal areas, between 120-200 ms after stimulus onset. VMMNs to changes from cardinal angles were larger and more sustained than vMMNs evoked by changes from oblique angles. Changes from cardinal orientations represent a more detectable signal for the automatic change detection system than changes from oblique angles, thus increased vMMN to these “larger” deviances might be considered a variant of the magnitude of deviance effect rarely observed in vMMN studies.